Racism and dehumanisation in Heart of Darkness and its Italian translations: A reader response analysis. (November 2019) - Mastropierro, Lorenzo; Conklin, Kathy
This article presents the results of a reader response study of Joseph Conrad's Heart of Darkness and two of its Italian translations. Specifically, data from an online questionnaire are used to test whether English and Italian readers respond differently to the potential racist implications of the fictional representation of the African natives. Whereas one translator removes completely all occurrences of nigger ( s ) and negro, the other adds additional uses of the slurs which are not present in the original. We explore with empirical methods whether these translational alterations have an effect on the readers' perception of dehumanisation, discrimination and racism in the text, comparing responses to each translation with responses to the original. Our findings not only show evidence of significant differences in the responses between one translation and the original but also suggest that other linguistic and extra-linguistic factors could be influencing readers' response. With this article, we aim to contribute to the under-researched application of reader response approaches to translation studies.